Investigating the effects of multimodal tasks-critical reading integrated instruction on rural senior high school students’ reading achievement, reading motivation and confidence in Hohhot Inner Mongolia, China - Yanru Wang; Pauline Swee Choo Goh; Mei Kin Tai (Journal of Research, Policy & Practice of Teachers & Teacher Education)
One of educational reforms that China is undertaking is to improve her citizen’s English language proficiency, and more specifically, to be competent in critical reading. However, there is a tendency to pay too much attention to grammar to improve students' reading comprehension, which may bring great reading pressure to students, but it will not improve their critical reading ability. This can be frustrating to the students and possibly affect their motivation to further pursue reading. In addition, a teacher-centered approach may have improved students’ vocabulary and grammatical rules, but not to read critically. Therefore, this study reports the effects of integrating critical reading content with multimodal tasks which aims at providing English Language teachers in China with an alternative approach for teaching critical reading. A quasi-experimental design with pretest and post-test is used to investigate the effects of multimodal tasks integrated lessons on Grade 2 rural senior high school students’ critical reading achievement. Their motivation and confidence is also examined. Two questionnaires are used to examine students’ motivation and confidence to read critically. The findings reveal that the experimental groups with the intervention of multimodal tasks has a higher critical reading test scores than the control groups. The questionnaires also show that the experimental group receiving multimodal task also has a significantly better motivation and confidence to read critically as compared to the control group after the intervention. Multimodal tasks have a positive impact on the critical reading ability, motivation and confidence.